Influence of single nucleotide polymorphism of LAT1 on therapeutic response to gabapentinoids in Pakistani patients with neuropathic pain. Issue 3 (12th December 2020) - Shaheen, Abida; Alam, Syed Mahboob; Azam, Fahad; Khan, Moosa; Ahmad Saleem, Salman; Liaquat, Afrose; Mumtaz, Sana
Abstract: Gabapentinoids are substrate of L‐type amino acid transporter 1 (LAT1) for distribution across the blood‐brain barrier. The present study aimed to evaluate the effect of LAT1 rs4240803 genetic polymorphism on the clinical efficacy and tolerability of gabapentinoids in Pakistani patients with neuropathic pain. Three‐hundred and ninety‐two patients were recruited, genotyped for SNP rs4240803, and followed up for eight weeks to evaluate the clinical response to gabapentinoids in terms of pain relief, inadequate response, and the emergence of adverse events. LAT1 rs4240803 GG, GA, and AA genotype frequency were 33.42%, 47.96% and 18.62%, respectively. Out of 392 patients, 323 responded to the treatment and 17.6% discontinued either due to insufficient response or intolerable adverse events (AEs). GA genotype was more frequent in non‐responder group ( P ˂ 0.001). Maximum pain responders (≥50%) in combination with the lowest incidence of AEs were observed in the GG group, whereas partial responders belonged to GA genotype and with the highest frequency of somnolence (83.6%) and dizziness (69.9%). Overall, 72.5% patients with GA genotype experienced AEs ( P ˂ 0.001). In conclusion, clinical outcomes of gabapentinoids are influenced by LAT1 rs4240803 polymorphism and population pharmacogenetics should be considered to evaluate the maximum potential of gabapentinoids in the management of neuropathic pain.